The Significance of Lontara Bilang as Local Historiography in the Kingdom of Gowa - Susmihara Susmihara; Nuraeni S; Lidya Megawati; Ahmad Habib Akramullah (Tarikhuna: Journal of History and History Education, 2025)
As a living archive of the past, Indonesian history serves as a bridge connecting the past and present to reveal the wisdom and diversity of its people across the archipelago. South Sulawesi, as an integral part of this historical inheritance, has developed its own distinct narrative, including the existence of the Gowa Kingdom as a preserver of ancient traditions. Therefore, this research aims to further investigate and promote the Lontara Bilang script to enhance and broaden awareness of the history and values inherent in the cultural heritage of South Sulawesi, particularly within the context of the Gowa Kingdom. This research is a qualitative exploration employing descriptive analysis techniques. Data were collected through library research, involving the analysis of materials from library sources. The research process comprised Heuristics, Source Criticism, Interpretation and Historiography. The finsings of this investigation indicate that the significance of Lontara Bilang extends beyond its use in writing within the kingdom. More significantly, Lontara Bilang has played a crucial role in maintaining, reinforcing and preserving Gowa’s rich and historic cultural identity. The preservation of Lontara Bilang, as a custodian of the history and cultural heritage of the people of the archipelago, particularly the people of Gowa, must be preserved for the future. It should serve as a cultural symbol that embodies the unique identity of the people of South Sulawesi, especially Makassar or the Kingdom of Gowa at that time. Therefore, Lontara Bilang provodes a solid foundation and reference for the development of knowledge and science in the future.